Gut metabolomics and 16S rRNA sequencing analysis of the effects of arecoline on non-alcoholic fatty liver disease in rats - Zhu, Lingping; Li, Duo; Yang, Xuefeng (Frontiers in Pharmacology, 2023)
Introduction: Non-alcoholic fatty liver disease (NAFLD) has gradually become the primary cause of fatty liver disease. Betel nuts have been used to treat gastrointestinal diseases. Methods: In the present study, we analyzed the pathology, serology, gut flora, and metabolites in a rat model of NAFLD, with and without betel nut alkaloid treatment, using an integrated approach involving pathology, serological testing, 16S rRNA gene sequencing, and ultra-performance liquid chromatography-mass spectrometry metabolomics. Results: Two rats were used for model validation. Thirty SD rats were included and divided into the normal group (C group), NAFLD model group (M group), low-dose group, medium-dose group (T group), and high-dose group with intraperitoneal injection of arecoline. The expression of blood lipids was significantly downregulated at all three arecoline concentrations (p < 0.05). Alpha-diversity analysis of the intestinal flora showed significant differences among the three groups, with a significant reduction in population diversity in the M group and a recovery of population diversity after arecoline treatment. At the phylum level, the relative abundance of Firmicutes was significantly higher in the T group and Proteobacteria in the M group. The KEGG metabolic pathways included polyketide sugar unit biosynthesis and hypertrophic cardiomyopathy. Thirty-three significantly different metabolites were identified among the groups. Significantly different metabolites between groups T and M included indolepyruvate, 2-deoxystreptamine, sakuranetin, glycyl-leucine, and riboflavin. The KEGG metabolic pathway suggested a potential role for arachidonic acid metabolism, serotonergic synapses, neuroactive ligand-receptor interactions, tyrosine metabolism, and regiomelanin. Vitamin digestion and absorption, as well as regulation of lipolysis in adipocytes, were the main metabolic pathways that distinguished the T vs. M groups. PGE2 is involved in several metabolic pathways. Correlation analysis showed that 29 bacterial species were significantly associated with PGE2 levels in the M and T groups. Vagococcus, Lawsonia, Christensenella, unidentified Erysipelotrichaceae, unidentified Coriobacteriaceae, and five other bacterial groups are unique in the PGE2 metabolic pathway regulated by arecoline. Discussion: Arecoline has lipid-lowering effects and may exert therapeutic effects in NAFLD through intestinal metabolites and intestinal flora, as well as through the Butyricicoccus/Christensenella/Coriobacteriaceae-COX2/PGE2 pathway. Thus, arecoline may represent a potential drug or target for NAFLD treatment.